Moral and Ethical Issues: Are they the Missing Links in University Programs? - María Eugenia Guerrero Useda; Diomedes Andrés Gómez Paternina (Universidad Autónoma de Baja California, 2013)
Now that there is greater consensus on the merit of teaching ethics and continuing the moral education of youth at the university level, it is necessary to determine what constitute core values and the pedagogical conditions necessary for teaching them. This article presents the results of research that attempts to establish the function effectively assigned to the teaching of ethics and moral education in the context of higher education. Based on documentary research, followed by a comparative study with theoretical sampling, we found that while 52% of the programs reviewed had at least one course related to the teaching of ethics, there were no contents geared specifically to the teaching of moral action. In law and medicine the trend toward professional ethics prevails, while engineering programs veer towards issues of social responsibility. Judging by our analysis of 120 course subjects, moral training of the individual is absent from university curricula.